2022
DOI: 10.3389/fonc.2022.999654
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of an immune-related lncRNAs signature to predict the overall survival of ovarian cancer

Abstract: Ovarian cancer (OC) is the most lethal gynecological cancer in women. Studies had reported that immune-related lncRNAs signatures were valuable in predicting the survival and prognosis of patients with various cancers. In our study, the prognostic value of immune-related lncRNAs was investigated in OC patients from TCGA-RNA-seq cohort (n=378) and HG-U133_Plus_2 cohort (n=590), respectively. Pearson correlation analysis was implemented to screen the immune-related lncRNA and then univariate Cox regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…We combined the TARGET and GTEx databases and used Pearson correlation analysis (coefficient set to >0.3, p value set to <0.001) to create a prognostic predictive signature for osteosarcoma comprising five lactate metabolism-associated lncRNAs for the first time based on the experience of previous scholars studying related lncRNAs [38] , [39] , [40] , [41] . In the correlation node network graph of the eight DELRLs, RP5-1011O1.2 was negatively correlated with other genes, while all other genes were positively correlated with each other, indicating that RP5-1011O1.2 may be a security gene for patients with osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…We combined the TARGET and GTEx databases and used Pearson correlation analysis (coefficient set to >0.3, p value set to <0.001) to create a prognostic predictive signature for osteosarcoma comprising five lactate metabolism-associated lncRNAs for the first time based on the experience of previous scholars studying related lncRNAs [38] , [39] , [40] , [41] . In the correlation node network graph of the eight DELRLs, RP5-1011O1.2 was negatively correlated with other genes, while all other genes were positively correlated with each other, indicating that RP5-1011O1.2 may be a security gene for patients with osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The ROC curves of different clinical factors and the FL_Score for predicting the 5-year survival rate (Figure 4E) showed that the AUC values of the FL_Score, age, and stage were 0.681, 0.578, and 0.65, respectively, indicating that FL_Score has a better capability to predict OV prognosis when compared with the other clinical factors. We also compared the 1-, 3-, and 5-year AUC values of FL_Score with 18 other published prognostic signatures [9,10,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] for patients with OV in TCGA database to test the prognostic performance of our FL_Score signature (Figure 5). These 18 signatures exhibited associations with some biological features, including N6-methyladenosine, pyroptosis, autophagy, and others.…”
Section: Model Construction and Validationmentioning
confidence: 99%
“…Many lncRNAs are involved in gene regulation and various biological functions at the transcriptional, posttranscriptional, and epigenetic levels, including the recent discovery that some lncRNAs can encode small peptides/proteins [ 6 ]. Accumulating evidence showed that aberrant expression of lncRNAs is not only associated with tumor malignancy but many chemically modified lncRNAs have been validated in various cancers [ 7 , 8 ]. There may be interactions between these modifications, with some competitive compensation.…”
Section: Introductionmentioning
confidence: 99%